From wonder to being: Metaphysical enchantment as an African Ratzingerian rejoinder to empirical reductivism - Callum D. Scott (Verbum et Ecclesia)
The post and/or modern humanity conceptualise their epistemic ability as providing the singular reliable interlocutor of knowing. However, implicit in this epistemology is modern humanity’s turning away from being qua being to a self-referential, relative and reductive modality of understanding. The ever-growing scientific corpus aids this view on post and/or modern epistemology, but by its success, this knowing has lessened other modes of knowing, e.g., metaphysics, indigenous knowledge systems, etc. In the post and/or modern milieu, the exploration of being is consequently not done on being’s own complex and irreducible terms but only on those construed by the subject. Inspired by the decolonial turn in the African academy and utilising the paradigm of African Philosophy and the Ratzingerian critique, the case is made that the influence of the seemingly opposing – but significantly coupled – reductive epistemological movements of modern empiricism and postmodern relativism have collaborated to disenchant the human experience. By ‘acceptable’ knowledge’s limitation to knowing relative to and/or measurable by the thinking subject, the post and/or modern subject is detached from being and becomes disenchanted in the divestment of wonder. It is contended that for the human to encounter being, wonder before the cosmos as-it-is, that is, the experience of enchantment, must be reclaimed for the sake of non-reductive and non-self-referential knowledge. By appealing to African decolonised epistemology and Aristotelian-Thomism, a more liberated conceptualisation of ‘science’ beyond the constraints of post and/or modern epistemology, incorporating the wondrous, is argued for.